Potensial Daerah Aliran Sungai di Jawa Barat yang Berpengaruh Terhadap Lumbung Pangan Nasional dengan Indikator Qmaximum/Qminimum - Budi Wicaksono; John Paulus Pantouw; Mekar Ageng Kinasti (LPPM, 2024)
The development of the times, especially the development of global climate change and the rapid increase in population in River Watershed areas, will influence the condition of the watershed. The increasing and excessive use of natural resources to meet human needs in watershed areas will result in several things, including increased land change, decreased soil capacity and disruption of water balance. High population growth rates will increase competition between providing land for food production and other needs. In line with population growth, the population's need for food is also increasing, because the size of the population is directly related to food supply. This research aims to analyze the potential size of 5 sub-watersheds in West Java which influence the national food storage, so that it is hoped that it can provide suggestions for ways out according to the characteristics of each sub-watershed in terms of strengthening national food security. From the results of research conducted on 5 sub-watersheds in West Java with indicators of the ratio between maximum discharge and minimum discharge (Qmax/Qmin), the results showed that the average value of the ratio between maximum discharge and minimum discharge (Qmax/Qmin) for the Citarik River -The buffer is 11.77 which is included in the